2018
DOI: 10.1016/j.jlumin.2018.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gallium content on Ga3+ position and photo- and thermally stimulated luminescence in Ce3+-doped multicomponent (Y,Lu)3GaxAl5-xO12 garnets

Abstract: Photoluminescence, thermally stimulated luminescence (TSL) and EPR characteristics of the Ce 3+ -doped single crystals of multicomponent Y1Lu2GaxAl5-xO12 and Lu3GaxAl5-xO12 garnets with different Ga contents (x = 0, 1, 2, 3, 4, 5) excited in the Ce 3+ -related absorption bands are investigated in the 9 -500 K temperature range. The distribution of Ga 3+ and Al 3+ ions in the crystal lattice is determined by the NMR method. The relative number of Ga 3+ ions in the tetrahedral crystal lattice sites, the maxima p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Therefore, it could also depend on the band gap energy E g of the host material and increase with increasing E g [154]. The best materials to investigate these dependences could be multicomponent garnets where both the CB edge energy and E g can be changed by variation of their composition (see, e.g., [194][195][196][197][198][199]). Let us consider some examples.…”
Section: On the Dependence Of The Uv/vis Emission Intensity Ratio On mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it could also depend on the band gap energy E g of the host material and increase with increasing E g [154]. The best materials to investigate these dependences could be multicomponent garnets where both the CB edge energy and E g can be changed by variation of their composition (see, e.g., [194][195][196][197][198][199]). Let us consider some examples.…”
Section: On the Dependence Of The Uv/vis Emission Intensity Ratio On mentioning
confidence: 99%
“…It was shown that the incorporation of the Ga 3+ ions results in a strong reduction of the band gap edge (by 1 eV from Y 3 Al 5 O 12 :Bi to Y 3 Ga 5 O 12 :Bi). In [195][196][197][198][199], it was shown that the increasing Ga content also results in a drastic decrease of the CB bottom energy in different Ce 3+ -doped multicomponent garnets. The presence of two-UV and VIS-emission bands in Y 3 Al 5 O 12 :Bi with the close lowest-energy excitation bands indicates that the triplet RES of Bi 3+ should be located close to the bottom of CB of Y 3 Al 5 O 12 [7].…”
Section: On the Dependence Of The Uv/vis Emission Intensity Ratio On mentioning
confidence: 99%
“…However, there was no EPR signals in the ZnO:Er(1%) NRA. Considering the EPR spectrometer sensitivity reaching about 10 12 spins (see Experimental Section) and the signal-to-noise ratio, practically, the concentration of spins, which could be reliably detected, is about tens of ppm . Therefore, one may expect the Er concentration to be lower than that in the NRF sample.…”
Section: Resultsmentioning
confidence: 99%
“…However, since changes in the persistent luminescence were observed with the increase in sintering pressure, the electron transfer through the conduction band should also be taken into account, where the distance from the trap depends on the pressure applied in the preparation process. In this case, the electrons excited from the ground level to the 5d state due to the relatively small thermal activation energy 43 are transferred through the conduction band to the traps (3). The activation energies ( E a(lp) and E a(hp) ) calculated from the TL glow curves were in the range of 0.58 to 0.69 eV (below the CB), which show that these defects are able to capture and release the electrons at room temperature.…”
Section: Resultsmentioning
confidence: 99%